2008
DOI: 10.1124/dmd.108.021725
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Binding and Tissue Distribution/Retention Assessment of Drugs Associated with Idiosyncratic Drug Toxicity

Abstract: ABSTRACT:Bioactivation of a drug to a reactive metabolite and its covalent binding to cellular macromolecules is believed to be involved in clinical adverse events, including idiosyncratic drug toxicities (IDTs). For the interpretation of the covalent binding data in terms of risk assessment, the in vitro and in vivo covalent binding data of a variety of drugs associated with IDTs or not were determined. Most of the "problematic" drugs, including "withdrawn" and "warning" drugs, exhibit higher human liver micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 27 publications
1
73
0
Order By: Relevance
“…Zia-Amirhosseini et al (1994) proposed that covalent binding of tolmetin to human proteins was through an acyl glucuronide, which reacted with proteins either via a nucleophilic displacement or a Schiff base intermediate. Acyl glucuronide-mediated covalent binding has also been reported for valproic acid and zomepirac (Takakusa et al, 2008). In this study, alkaline digestion of human plasma protein pellets released eltrombopag in addition to M1 (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Zia-Amirhosseini et al (1994) proposed that covalent binding of tolmetin to human proteins was through an acyl glucuronide, which reacted with proteins either via a nucleophilic displacement or a Schiff base intermediate. Acyl glucuronide-mediated covalent binding has also been reported for valproic acid and zomepirac (Takakusa et al, 2008). In this study, alkaline digestion of human plasma protein pellets released eltrombopag in addition to M1 (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…The skin toxicity and allergic reactions observed with nevirapine are rather ascribed to its metabolite, 12-hydroxynevirapine (62), which can be further transformed into a QM (63). However, the relationship between a QM derived from nevirapine and these side effects is just hypothesized [80].…”
Section: An Update About Qms and Cancermentioning
confidence: 99%
“…A QM (63) that is derived from the hydroxymethyl metabolite of NEV had been identified previously [62]. Although it is not the only electrophilic compound generated, it could participate in the generation of the NEV adducts that were detected in the liver tissue of treated patients [63].…”
Section: Examples Of Chemically-derived Qmsmentioning
confidence: 99%
“…Earlier investigations of whether CB can estimate DILI were performed with positive drugs (Evans et al, 2004;Masubuchi et al, 2007;Takakusa et al, 2008), but only a few researchers have made comparisons with examples of safe drugs. However, it was recently reported that the total daily dose of drugs improves the discrimination between hepatotoxic and nontoxic drugs based on in vitro CB intrinsic clearance (Obach et al, 2008;Bauman et al, 2009).…”
Section: Evaluation Of Drug-induced Liver Injury By Covalent Bindingmentioning
confidence: 99%